Health and fitness of postmenopausal women in urban versus rural gurugram: A cross-sectional study - Puneeta Ajmera; Sheetal Kalra; Sadhu Charan Mohapatra; Joginder Yadav (Wolters Kluwer Medknow Publications, 2022)
Context: Throughout that process of menopause, a slew of health and fitness problems arise, all of which have a major effect on a woman's standard of living. Health-related physical fitness has been described as an individual's cardiac fitness (aerobic capacity), musculoskeletal fitness, and body composition. Aim: To investigate and compare the health and fitness of postmenopausal women in rural and urban Gurugram. Settings and Design: The postmenopausal women of Gurugram, both urban (n = 175) and rural (n = 175), who attended the outpatient department of SGT Hospital in the urban area and a house-to-house survey in the rural area, were the subjects of a cross-sectional survey that was carried out using interviews and a pretested semi-structured questionnaire. Levels of physical activity (PA) were assessed using the International PA Questionnaire (short form). The evaluation of body composition, which was the following step, included determining one's body mass index, waist circumference, and waist-hip ratio. Six-minute Walk Distance Test was used to assess cardiopulmonary fitness. Through chair squat tests, sit-and-reach tests, and grip tests, researchers were able to measure the lower limb strength, flexibility, and upper limb strength of participants. Results: The mean age of subjects was 53.61 ± 5.08 years. Most commonly reported health problems were hypertension (31.3%), hyperlipidemia (21.2%), and diabetes (13.4%). Odds of urban women developing hypertension, hyperlipidemia, and myocardial infarction (MI) were found to be 0.61, 0.42, and 0.96 times higher than rural women. There was a statistically significant difference for the squat test, grip test, body composition parameters, and aerobic capacity; however, no statistically significant difference was seen for sit-and-reach test (P > 0.05). Conclusions: The current research shows that postmenopausal women living in metropolitan areas may face higher health risks since they are more prone to develop hypertension, hyperlipidemia, and MI. Furthermore, all fitness metrics - aside from flexibility - were higher for rural women. The results of the current study highlight the urgent need for health promotion initiatives to enhance the health and fitness of urban postmenopausal women.